Simultaneous Occurring Heatwaves and Cyanobacteria Blooms Alter Polyunsaturated Fatty Acid Transfer in a Brackish Trophic Cascade - Alexander Wacker; Melanie E. Köhne; Laura M. Wienhausen; Ilka Carina Stephan (Journal of Marine Science and Engineering, 2026)
With climate change, marine heatwaves become more frequent and may favour the emergence of cyanobacterial blooms. Because cyanobacteria lack long-chain polyunsaturated fatty acids, they provide poor dietary quality for consumers, potentially altering the fatty acid composition of primary consumers and propagating nutritional stress through food webs. We examined how a simulated heatwave (12 °C to 18 °C) and an associated cyanobacterial bloom-like dominance may affect trophic transfer from phytoplankton to the herbivorous rotifer Brachionus plicatilis and further to its predator, the mysid Neomysis integer. Rotifers were fed either high-quality algae or a low-quality cyanobacteria-dominated diet mixture. Rotifers were then rinsed to remove external residual phytoplankton and subsequently offered as prey to mysids. We analyzed the fatty acid profiles of both rotifers and mysids and monitored mysid survival. High temperature and the presence of cyanobacteria at the base of the food web reduced mysid survival. Both factors also influenced the fatty acid composition of rotifers and mysids. For mysids at the third trophic level, warming modulated how strongly diet quality affected their fatty acid profile. These results suggest that concurrent heatwaves and cyanobacterial blooms may intensify cyanobacteria’s negative impacts on food webs by altering the transfer of key fatty acids across trophic levels.

Spring heatwaves intensify negative effects by cyanobacteria blooms on polyunsaturated fatty acids of a brackish zooplankter - Laura M. Wienhausen; Marvin Kiene; Alexander Wacker (Limnology and Oceanography, 2026)
Marine heatwaves are projected to occur more frequently in near future and can favor the occurrence of cyanobacteria blooms. Cyanobacteria typically provide low dietary quality for consumers due to their lack of long‐chain polyunsaturated fatty acids (LC‐PUFA). This can alter the fatty acid composition of their primary consumers and trigger cascading effects throughout the food chain. In this study, we investigated the combined effects of a simulated spring heatwave and associated cyanobacteria bloom on intrinsic growth rates and fatty acid compositions of the zooplankter Brachionus plicatilis . The rotifers were fed three diets differing in quality and temporal occurrence, with (1) permanent high (“H”), (2) permanent low quality (“L”), or with (3) a diet switch from high to low quality, mimicking a cyanobacteria bloom (“CB”). Rotifers of each food treatment were additionally exposed to either ambient temperature (12°C, “‐HW”) or spring heatwave conditions (18°C, “+HW”). Population growth rates increased under heatwave conditions for all diets. Food quality affected fatty acids, both quantitatively and qualitatively. H rotifers showed highest contents of fatty acids and LC‐PUFA. The fatty acids of CB rotifers resembled those of L rotifers, indicating rotifers could not maintain their fatty acid compositions during a 5‐d cyanobacteria bloom. Most importantly, the simulated heatwave intensified diet‐mediated fatty acid differences, benefiting H rotifers but not L or CB rotifers. Therefore, the cyanobacteria bloom accompanied by warming resulted in fewer PUFA in rotifers. We thus conclude that the projected increasing occurrence of heatwaves can aggravate cyanobacteria's negative impacts on future food webs.

A Radiocarbon‐Based Framework to Assess Soil Organic Carbon Persistence and Vulnerability Across Land‐Use Types - Luisa I. Minich; Jeffrey Beem‐Miller; Benedict V. A. Mittelbach; Dylan Geissbühler; Annegret Udke; Daniel Wasner; Margaux Moreno Duborgel; Ciriaco McMackin; Alexander S. Brunmayr; Lukas Wacker; Philip Gautschi; Negar Haghipour; et al. (Global Change Biology, 2026)
Soil organic carbon (SOC) can persist from days to millennia but remains vulnerable to carbon (C) loss upon disturbances, depending on environmental conditions and mode of stabilization. Understanding drivers of persistence and vulnerability is crucial to assess soil C sequestration as well as potential SOC losses due to changes in climate and land use. Here, we investigate SOC persistence and vulnerability in five land‐use types by combining radiocarbon‐derived estimates of SOC age (system age) and age of respired CO 2 (transit time) with indicators of biological (SOC decomposability) and thermal stability (residual oxidisable carbon content, ROC). Based on this, we developed a vulnerability index for SOC and applied it across soil profiles from 19 sites representing temperate and alpine grasslands, forests, croplands, and managed peatlands. Transit times and system ages ranged from 2 years in the organic layer of forests to 5760 years in subsoils of managed peatlands and varied significantly across land‐use types and soil depth. Transit times were generally shorter than system ages, indicating that soil‐respired CO 2 is dominated by more recent inputs, while bulk SOC contains more persistent C. In forests, temperate grasslands, and croplands, system ages were positively linked to thermal stability and mineral reactivity, indicating higher SOC persistence through organo‐mineral stabilization. In contrast, alpine grasslands and managed peatlands showed centennial to millennial system ages despite low thermal stability ( 90 kg m −2 in managed peatlands), this implies a high vulnerability of these soils to environmental disturbances that alleviate these constraints. Our findings demonstrate that combining metrics of biological and thermal stability with radiocarbon data provides a powerful framework to assess SOC vulnerability to disturbances induced by environmental change.

Hypoosmotic stress might endanger survival of the mysid Neomysis integer despite activation of ion transport ATPases - Konstanze Brinkop; Elisa Lehmann; Jan-Peter Hildebrandt; Alexander Wacker (Journal of Experimental Marine Biology and Ecology, 2026)

The role of light quality and species richness in shaping phytoplankton communities - Vanessa Marzetz; Aaron Katz; Julia Wuthe; Maren Striebel; Alexander Wacker (Limnology and Oceanography, 2025)
In natural water bodies, the light spectrum changes with depth, often toward a higher proportion of blue light. While spectral niche partitioning and functional redundancy are important concepts, our understanding of how light spectrum changes affect phytoplankton communities is limited. To understand how phytoplankton respond to changes in spectral light availability, we studied the effects of light quality on species growth, community composition, and biomass production. In a controlled laboratory experiment, we assembled up to 7 phytoplankton species into 13 communities with 5 different initial species richness levels. Communities were exposed to three light quality treatments simulating the red light reduction across water depths (full spectrum, reduced red proportion, and no red). Community biomass was positively influenced by the initial number of species, and this was most pronounced if red light was reduced (shown by a significant interactive effect of light conditions and initial species richness). The growth rate responses were highly species specific, and among the species tested, only Chlamydomonas showed increased growth rates with higher blue light levels, while most others exhibited negative trends. Initial species richness significantly influenced these outcomes. By the end of the experiment, Chlamydomonas had increased in proportion within the community, demonstrating its competitive strength and ability to affect the growth of other species. Our study highlights the sensitivity of certain species to specific wavelengths of light and how competition can shape these responses, contributing to a better understanding of phytoplankton dynamics in changing aquatic environments.

Ingestion and respiration rates of a common coastal mysid respond differently to diurnal temperature fluctuation - Konstanze Brinkop; Laura M. Wienhausen; Erik Sperfeld; Alexander Wacker (Limnology and Oceanography, 2024)
Animals face strong environmental variability even on short time scales particularly in shallow coastal habitats, forcing them to permanently adjust their metabolism. Respiration rates of aquatic ectotherms are directly influenced by water temperature, whereas ingestion rates might additionally be influenced by behavior. We aim to understand how respiration and ingestion rates of an aquatic invertebrate respond to changing temperature during a diurnal thermal fluctuation cycle and how both processes are related. We studied the benthopelagic mysid Neomysis integer as an important food web component of coastal ecosystems. Mysids were collected at the southern Baltic Sea coast and exposed in the laboratory to either constant temperature of 15°C or daily temperature fluctuation of 15 ± 5°C. Short‐term (1–2 h) respiration and ingestion rates were measured at four equidistant time points within 24 h and did not differ among time points at constant temperature, but differed among time points in the fluctuating treatment. Respiration was highest at the thermal maximum and lowest at the thermal minimum. Ingestion rates showed the opposite pattern under fluctuation, likely due to differences in underlying thermal performance curves. When temperature transited the average, the direction of temperature change influenced the animals' response in respiration and ingestion rates differently. Our results suggest that respiration is not only instantaneously affected by temperature, but also influenced by the previously experienced direction of thermal change. Our experiment, using an important non‐model organism, delivered new insights on the relationship between the crucial organismal processes ingestion and respiration under thermal variability.

Sudden disappearance of yew (Taxus baccata) woodlands from eastern England coincides with a possible climate event around 4.2 ka ago - Tatiana Bebchuk; Paul J. Krusic; Joshua H. Pike; Alma Piermattei; Ronny Friedrich; Lukas Wacker; Alan Crivellaro; Tito Arosio; Alexander V. Kirdyanov; Philip Gibbard; David Brown; Jan Esper; et al. (Quaternary Science Reviews, 2024)

Interactive effects of nitrogen and phosphorus on growth and stoichiometry of lake phytoplankton - Paul C. Frost; Nolan J. T. Pearce; Stella A. Berger; Mark O. Gessner; A. Katharina Makower; Vanessa Marzetz; Jens C. Nejstgaard; Aljona Pralle; Svenja Schälicke; Alexander Wacker; Nicole D. Wagner; Marguerite A. Xenopoulos (Limnology and Oceanography, 2023)
Phytoplankton responses to nutrient enrichment are often assumed to be universal, but in practice they can significantly vary because the effect size to an increased supply of one nutrient may depend on the availability of the other. Here, we used two complementary two‐way factorial experiments to determine how responses of lake phytoplankton to increased N and P supply vary with increasing concentrations of the other nutrient. We manipulated dissolved N and P concentrations in a 4‐d bioassay conducted with lake phytoplankton and measured/determined chlorophyll a and carbon (C)‐specific growth rates, phytoplankton size‐classes, chlorophyll‐specific N and P removal, and seston C : N : P ratios. These data were used to assess the presence and type of interactive effects between N and P on phytoplankton. For most response variables, the effects of increased N supply depended on the background concentration of P and vice versa. The specific nature of effects differed among response variables and depended on the N and P concentrations present in the bioassay. Generally, increases of N or P alone elicited few and weaker effects than increasing the supply of one element in combination with the other. Overall, our results show that phytoplankton responses to increased N or P supplies are context dependent and likely reflect multiple processes involved in nutrient uptake and use. These results also show that phytoplankton responses to N and P supply ratios can depend on the supply rate of the other nutrient, which complicates understanding how single nutrient enrichment affects lake phytoplankton producers.

Thermal Fluctuations Yield Sex-Specific Differences of Ingestion Rates of the Littoral Mysid Neomysis integer - Laura M. Hennigs; Konstanze Bergunder; Erik Sperfeld; Alexander Wacker (Frontiers in Marine Science, 2022)
Shallow aquatic environments are characterized by strong environmental variability. For ectotherms, temperature is the main driver of metabolic activity, thus also shaping performance. Ingestion rates in mysids are fast responses, influenced by metabolic and behavioral activity. We examined ingestion rates of the mysid Neomysis integer , collected in the Baltic Sea, after one-week exposure to different constant and fluctuating temperature regimes (5, 10, 15, 20°C and 9 ± 5, 14 ± 5°C, respectively). To investigate possible differences between sexes, thermal performance curves (TPCs) were established for female and male mysids based on ingestion rates measured at constant temperatures. TPCs of ingestion rates at constant temperatures differed between sexes, with female mysids showing a higher total ingestion rate as well as a higher thermal optimum compared to male mysids. Females showed reduced ingestion rates when exposed to fluctuating temperatures around their thermal optimum, whereas ingestion of male mysids was not reduced when exposed to fluctuating temperatures. The observed sex-specific differences might be related to potentially higher lipid and energy demands of the females. We suggest future studies should investigate males and females to improve our understanding about impacts of environmental variability on natural populations.

The distribution of lagomorph syphilis caused by Treponema paraluisleporidarum in Europe - Linda Hisgen; Lena Abel; Luisa Hallmaier-Wacker; Simone Lüert; Antonio Lavazza; Tiziana Trogu; Roser Velarde; Markéta Nováková; Miklós Gyuranecz; Erik Ågren; Alexander Barlow; David Šmajs; et al. (European Journal of Wildlife Research, 2021)
Treponema paraluisleporidarum infects both rabbits (ecovar Cuniculus) and hares (ecovar Lepus). While the occurrence of the bacterium has previously been reported for European brown hares ( Lepus europaeus ) and domestic rabbits ( Oryctolagus cuniculus f. domestica ), there are no data available that report infection in the European context. We tested a total of 1,995 serum samples and 287 genital swabs from opportunistically sampled European brown hares ( Lepus europaeus ; n = 2135), Mountain hares ( Lepus timidus ; n = 4), European rabbits ( Oryctolagus cuniculus ; n = 138), and pet rabbits ( O. cuniculus f. domestica ; n = 5). The samples originated from eight European countries. In case only serum was available, we tested the samples for the presence of anti-treponemal antibodies. For this, we utilized the Treponema pallidum -particle agglutination test (TP-PA), which is suited for the use in lagomorphs due to the antigenic cross-reactivity of anti- T. pallidum and anti- T. paraluisleporidarum antibodies . In addition, the results of 380 sera were confirmed using the fluorescent- Treponema antibody absorption test (FTA-ABS). In all cases where swab samples were available, DNA was extracted and tested using quantitative PCR to test for the presence of the lagomorph syphilis-bacterium. We were able to detect antibodies in 825 of 1,995 lagomorph sera (41.4%; brown hare: 825/1,868; rabbit: 0/127) and obtained positive qPCR results from 182 of 287 swab samples (63.4%; European brown hare: 167/267; mountain hare: 4/4; rabbit: 11/16). While all rabbit sera ( n = 127) tested negative for anti-treponemal antibodies, the presence of the bacterium was confirmed in eight wild ( n = 8/11) and three domestic rabbits ( n = 3/5) from Germany using qPCR.

Plant–soil feedback effects altered by aboveground herbivory explain plant species abundance in the landscape - Johannes Heinze; Alexander Wacker; Andrew Kulmatiski (Ecology, 2020)
Relatively little is known about how plant–soil feedbacks (PSFs) may affect plant growth in field conditions where factors such as herbivory may be important. Using a potted experiment in a grassland, we measured PSFs with and without aboveground insect herbivory for 20 plant species. We then compared PSF values to plant landscape abundance. Aboveground herbivory had a large negative effect on PSF values. For 15 of 20 species, PSFs were more negative with herbivory than without. This occurred because plant biomass on “home” soils was smaller with herbivory than without. PSF values with herbivory were correlated with plant landscape abundance, whereas PSF values without herbivory were not. Shoot nitrogen concentrations suggested that plants create soils that increase nitrogen uptake, but that greater shoot nitrogen values increase herbivory and that the net effect of positive PSF and greater aboveground herbivory is less aboveground biomass. Results provided clear evidence that PSFs alone have limited power in explaining species abundances and that herbivory has stronger effects on plant biomass and growth on the landscape. Our results provide a potential explanation for observed differences between greenhouse and field PSF experiments and suggest that PSF experiments need to consider important biotic interactions, like aboveground herbivory, particularly when the goal of PSF research is to understand plant growth in field conditions.

The relative importance of plant-soil feedbacks for plant-species performance increases with decreasing intensity of herbivory - Johannes Heinze; Nadja K. Simons; Sebastian Seibold; Alexander Wacker; Guntram Weithoff; Martin M. Gossner; Daniel Prati; T. Martijn Bezemer; Jasmin Joshi (Oecologia, 2019)

Feeding in the frequency domain: coarser‐grained environments increase consumer sensitivity to resource variability, covariance and phase - Apostolos‐Manuel Koussoroplis; Svenja Schälicke; Michael Raatz; Moritz Bach; Alexander Wacker (Ecology Letters, 2019)
Theory predicts that resource variability hinders consumer performance. How this effect depends on the temporal structure of resource fluctuations encountered by individuals remains poorly understood. Combining modelling and growth experiments with Daphnia magna , we decompose the complexity of resource fluctuations and test the effect of resource variance, supply peak timing (i.e. phase) and co‐limiting resource covariance along a gradient from high to low frequencies reflecting fine‐ to coarse‐grained environments. Our results show that resource storage can buffer growth at high frequencies, but yields a sensitivity of growth to resource peak timing at lower ones. When two resources covary, negative covariance causes stronger growth depression at low frequencies. However, negative covariance might be beneficial at intermediate frequencies, an effect that can be explained by digestive acclimation. Our study provides a mechanistic basis for understanding how alterations of the environmental grain size affect consumers experiencing variable nutritional quality in nature.

Photosynthetic sensitivity of phytoplankton to commonly used pharmaceuticals and its dependence on cellular phosphorus status - Malgorzata Grzesiuk; Alexander Wacker; Elly Spijkerman (Ecotoxicology, 2016)

Covariance modulates the effect of joint temperature and food variance on ectotherm life‐history traits - Apostolos‐Manuel Koussoroplis; Alexander Wacker (Ecology Letters, 2016)
Understanding animal performance in heterogeneous or variable environments is a central question in ecology. We combine modelling and experiments to test how temperature and food availability variance jointly affect life‐history traits of ectotherms. The model predicts that as mean temperatures move away from the ectotherm's thermal optimum, the effect size of joint thermal and food variance should become increasingly sensitive to their covariance. Below the thermal optimum, performance should be positively correlated with food–temperature covariance and the opposite is predicted above it. At lower temperatures, covariance should determine whether food and temperature variance increases or decreases performance compared to constant conditions. Somewhat stronger than predicted, the covariance effect below the thermal optimum was confirmed experimentally on an aquatic ectotherm ( Daphnia magna ) exposed to diurnal food and temperature variance with different amounts of covariance. Our findings have important implications for understanding ectotherm responses to climate‐driven alterations of thermal mean and variance.

Bridging factorial and gradient concepts of resource co‐limitation: towards a general framework applied to consumers - Erik Sperfeld; David Raubenheimer; Alexander Wacker (Ecology Letters, 2016)
Organism growth can be limited either by a single resource or by multiple resources simultaneously (co‐limitation). Efforts to characterise co‐limitation have generated two influential approaches. One approach uses limitation scenarios of factorial growth assays to distinguish specific types of co‐limitation; the other uses growth responses spanned over a continuous, multi‐dimensional resource space to characterise different types of response surfaces. Both approaches have been useful in investigating particular aspects of co‐limitation, but a synthesis is needed to stimulate development of this recent research area. We address this gap by integrating the two approaches, thereby presenting a more general framework of co‐limitation. We found that various factorial (co‐)limitation scenarios can emerge in different response surface types based on continuous availabilities of essential or substitutable resources. We tested our conceptual co‐limitation framework on data sets of published and unpublished studies examining the limitation of two herbivorous consumers in a two‐dimensional resource space. The experimental data corroborate the predictions, suggesting a general applicability of our co‐limitation framework to generalist consumers and potentially also to other organisms. The presented framework might give insight into mechanisms that underlie co‐limitation responses and thus can be a seminal starting point for evaluating co‐limitation patterns in experiments and nature.

Interspecific competition in phytoplankton drives the availability of essential mineral and biochemical nutrients - Alexander Wacker; Vanessa Marzetz; Elly Spijkerman (Ecology, 2015)
The underlying mechanisms and consequences of competition and diversity are central themes in ecology. A higher diversity of primary producers often results in higher resource use efficiency in aquatic and terrestrial ecosystems. This may result in more food for consumers on one hand, while, on the other hand, it can also result in a decreased food quality for consumers; higher biomass combined with the same availability of the limiting compound directly reduces the dietary proportion of the limiting compound. Here we tested whether and how interspecific competition in phytoplankton communities leads to changes in resource use efficiency and cellular concentrations of nutrients and fatty acids. The measured particulate carbon : phosphorus ratios (C:P) and fatty acid concentrations in the communities were compared to the theoretically expected ratios and concentrations of measurements on simultaneously running monocultures. With interspecific competition, phytoplankton communities had higher concentrations of the monounsaturated fatty acid oleic acid and also much higher concentrations of the ecologically and physiologically relevant long‐chain polyunsaturated fatty acid eicosapentaenoic acid than expected concentrations based on monocultures. Such higher availability of essential fatty acids may contribute to the positive relationship between phytoplankton diversity and zooplankton growth, and may compensate limitations by mineral nutrients in higher trophic levels.

Maternal diet of Daphnia magna affects offspring growth responses to supplementation with particular polyunsaturated fatty acids - Erik Sperfeld; Alexander Wacker (Hydrobiologia, 2015)

Constraints by oxygen and food quality on carbon pathway regulation: a co‐limitation study with an aquatic key herbivore - Marcus Lukas; Alexander Wacker (Ecology, 2014)
In food webs, herbivores are often constrained by low food quality in terms of mineral and biochemical limitations, which in aquatic ecosystems can co‐occur with limited oxygen conditions. As low food quality implies that carbon (C) is available in excess, and therefore a regulation to get rid of excess C is crucial for the performance of consumers, we examined the C pathways (ingestion, feces release, excretion, and respiration) of a planktonic key herbivore ( Daphnia magna ). We tested whether consumer C pathways increase due to mineral (phosphorus, P) or biochemical (cholesterol and fatty acid) limitations and how these regulations vary when in addition oxygen is low. Under such conditions, at least the capability of the upregulation of respiration may be restricted. Furthermore, we discussed the potential role of the oxygen‐transporting protein hemoglobin (Hb) in the regulation of C budgets. Different food quality constraints led to certain C regulation patterns to increase the removal of excess dietary C: P‐limited D. magna increased excretion and respiration, while cholesterol‐limited Daphnia in addition upregulated the release of feces. In contrast, the regulative effort was low and only feces release increased when D. magna was limited by a long‐chain polyunsaturated fatty acid (eicosapentaenoic acid, EPA). Co‐limiting oxygen did not always impact the discharge of excess C. We found the food‐quality‐induced upregulation of respiration was still present at low oxygen. In contrast, higher excretion of excess C was diminished at low oxygen supply. Besides the effect that the Hb concentration increased under low oxygen, our results indicate a low food‐quality‐induced increase in the Hb content of the animals. Overall, C budgeting is phenotypically plastic towards different (co‐)limiting scenarios. These trigger specific regulation responses that could be the result of evolutionary adaptations.

Thresholds for Sterol-Limited Growth of Daphnia magna: A Comparative Approach Using 10 Different Sterols - Dominik Martin-Creuzburg; Sarah Oexle; Alexander Wacker (Journal of Chemical Ecology, 2014)

Nutritional indicators and their uses in ecology - Nicole D. Wagner; Helmut Hillebrand; Alexander Wacker; Paul C. Frost (Ecology Letters, 2013)
The nutrition of animal consumers is an important regulator of ecological processes due to its effects on their physiology, life‐history and behaviour. Understanding the ecological effects of poor nutrition depends on correctly diagnosing the nature and strength of nutritional limitation. Despite the need to assess nutritional limitation, current approaches to delineating nutritional constraints can be non‐specific and imprecise. Here, we consider the need and potential to develop new complementary approaches to the study of nutritional constraints on animal consumers by studying and using a suite of established and emerging biochemical and molecular responses. These nutritional indicators include gene expression, transcript regulators, protein profiling and activity, and gross biochemical and elemental composition. The potential applications of nutritional indicators to ecological studies are highlighted to demonstrate the value that this approach would have to future studies in community and ecosystem ecology.

Dietary lipid quality affects temperature-mediated reaction norms of a freshwater key herbivore - Dominik Martin-Creuzburg; Alexander Wacker; Christine Ziese; Martin J. Kainz (Oecologia, 2012)

Multiple resource limitation theory applied to herbivorous consumers: Liebig’s minimum rule vs. interactive co‐limitation - Erik Sperfeld; Dominik Martin‐Creuzburg; Alexander Wacker (Ecology Letters, 2012)
Ecology Letters (2011) Abstract There is growing consensus that the growth of herbivorous consumers is frequently limited by more than one nutrient simultaneously. This understanding, however, is based primarily on theoretical considerations and the applicability of existing concepts of co‐limitation has rarely been tested experimentally. Here, we assessed the suitability of two contrasting concepts of resource limitation, i.e. Liebig’s minimum rule and the multiple limitation hypothesis, to describe nutrient‐dependent growth responses of a freshwater herbivore ( Daphnia magna ) in a system with two potentially limiting nutrients (cholesterol and eicosapentaenoic acid). The results indicated that these essential nutrients interact, and do not strictly follow Liebig’s minimum rule, which consistently overestimates growth at co‐limiting conditions and thus is not applicable to describe multiple nutrient limitation of herbivorous consumers. We infer that the outcome of resource‐based modelling approaches assessing herbivore population dynamics strongly depends on the applied concept of co‐limitation.

Interactions between P-limitation and different C conditions on the fatty acid composition of an extremophile microalga - Elly Spijkerman; Alexander Wacker (Extremophiles, 2011)

Temperature‐ and cholesterol‐induced changes in eicosapentaenoic acid limitation of Daphnia magna determined by a promising method to estimate growth saturation thresholds - Erik Sperfeld; Alexander Wacker (Limnology and Oceanography, 2011)
We present data on eicosapentaenoic acid (EPA)‐limited growth responses of Daphnia magna under different temperatures and different dietary cholesterol availabilities to assess how EPA growth saturation thresholds depend on changing environmental conditions. D. magna was raised on gradients of dietary EPA at 15°C and 20°C with high cholesterol supply and at 20°C with low and high cholesterol supply in laboratory experiments. A new method was applied to estimate EPA growth saturation thresholds on the basis of fitted saturation curves using bootstrapped data. The EPA threshold at which 75% and 90% of maximum growth was reached ranged from 0.7 to 1.6 μg EPA (mg dietary C) −1 and 2.0 to 4.9 μg EPA (mg dietary C) −1 , respectively. Previously reported EPA concentrations in natural seston of many different lakes suggest that the thresholds measured here indicate a frequent potential for at least moderate EPA limitation in nature. Furthermore, the calculated EPA thresholds were higher in treatments of low compared with high temperature and higher in treatments of low compared with high cholesterol availability. The EPA‐dependent growth responses were more strongly affected by temperature than by cholesterol availability. Our results suggest that EPA growth saturation thresholds for a particular Daphnia species probably vary in nature under different environmental conditions.

Interactions between limiting nutrients: Consequences for somatic and population growth of Daphnia magna - Dominik Martin-Creuzburg; Alexander Wacker; Timo Basena (Limnology and Oceanography, 2010)
To assess the significance of nutrient interactions on animal performance, life‐history experiments were conducted with the freshwater herbivore Daphnia magna in a system with two limiting nutrients (i.e., sterols and polyunsaturated fatty acids [PUFAs]). By experimentally increasing the availability of dietary cholesterol either in the absence or in the presence of different dietary PUFAs we investigated whether dietary PUFAs differ in their potential to affect the sterol‐limited growth kinetics of the herbivore. Sterol‐limited growth responses of D. magna were characterized by a higher initial slope of the saturation curves and lower threshold concentrations in the presence of dietary PUFAs. This suggests significant interactions between limiting nutrients and lower dietary sterol requirements in the presence of dietary PUFAs. In contrast to somatic growth rates, which were significantly increased only by additional supplementation with eicosapentaenoic acid (EPA), population growth rates were significantly affected by additional supplementation with linoleic acid, α‐linolenic acid, docosahexaenoic acid (DHA), and in particular EPA and arachidonic acid. The fatty acid composition of D. magna reflected that of their diet. However, animals fed the DHA supplemented diet contained considerable amounts of EPA, indicating a retro‐conversion of DHA into EPA within their metabolism. The fitness of resource‐limited consumers is strongly affected by complex interactions between limiting nutrients and this topic has to be considered in experimental and theoretical studies investigating nutrient‐limited growth responses of animals to accurately assess consequences for population dynamics.

Male territorial aggression and androgen modulation in high latitude populations of the Sooty, Passerella iliaca sinuosa, and Red Fox Sparrow, Passerella iliaca zaboria - Douglas W. Wacker; Alexander J. Coverdill; Carolyn M. Bauer; John C. Wingfield (Journal of Ornithology, 2010)

Food quality controls egg quality of the zebra mussel Dreissena polymorpha : The role of fatty acids - Alexander Wacker; Eric von Elert (Limnology and Oceanography, 2004)
We investigated the investment of adult Dreissena polymorpha to the eggs by sampling mussels monthly from 4‐ and 15−m water depth. The fatty acid composition of eggs differed significantly between depths and over time. To assess whether temperature and food conditions led to the differences observed for mussels sampled from the two depths, mussels were reared in the laboratory under two different 3‐month temperature regimes, simulating the temperature of the lake at 4− and 15−m depth. Possible effects of food quality were tested in each simulation using four diets differing in fatty acid composition: Cryptomonas erosa , Nannochloropsis limnetica [rich in polyunsaturated fatty acids (PUFAs) and long‐chained PUFAs (≫C18)], Scenedesmus obliquus , and the cyanobacterium Aphanothece sp. (deficient in long‐chained PUFAs). In newly released eggs, specific (n‐3) and (n‐6) long‐chained PUFAs increased when these fatty acids were available in the natural seston or in the laboratory diets. Mussels fed organisms deficient in long‐chained PUFAs were still able to allocate arachidonic acid, eicosapentaenoic acid, and docosahexaenoic acid into eggs, which suggests that minimum levels of particular fatty acids were maintained in eggs by transfer from internal reserves of the female mussels to oocytes. In contrast to the diet, there were no effects of the temperature on the fatty acid composition of eggs.

Food quality controls reproduction of the zebra mussel (Dreissena polymorpha) - Alexander Wacker; Eric von Elert (Oecologia, 2003)

Food quality effects of unsaturated fatty acids on larvae of the zebra mussel Dreissena polymorpha - Alexander Wacker; Paul Becher; Eric von Elert (Limnology and Oceanography, 2002)
In standardized growth experiments, newly hatched larvae of the zebra mussel Dreissena polymorph a were fed diets representing different biochemical compositions. Algae that were rich in (n‐3) polyunsaturated fatty acids (PUFAs), except for long‐chained (>C18) PUFAs ( Chlorella minutissima and Monoraphidium minutum ) were of low food quality. Higher growth than on C. minutissima or M. minutum was supported by a culture of the cyanobacterium Aphanothece sp., which contained traces of a long‐chained (n‐3) PUFA, docosahexaenoic acid (DHA, 22 : 6n‐3). The alga Isochrysis aff. galbana , which contained high amounts of the longchained (n‐3) PUFAs DHA and eicosapentaenoic acid (EPA, 20 : 5n‐3), supported the highest growth. The alga Nannochloropsis limnetica , which differed from I. galbana by a deficiency in DHA, allowed slightly, but significantly lower, growth. Growth of larvae on N. limnetica was increased by enrichment of N. limnetica cells with a lipid extract of I. galbana , showing that larval growth on N. limnetica was limited by the deficiency of a compound that was present in I. galban a. Growth was also enhanced by feeding N. limnetica cells supplemented with DHA, but not by cells enriched with EPA, indicating that DHA was the limiting factor. We conclude that, on DHA‐deficient food, the larvae of D. polymorpha were not able to sufficiently convert C18‐PUFAs into long‐chained (n‐3) PUFAs and that the rates for elongation and desaturation of EPA into DHA limited growth.